"Sowing the Story": Narrative Identity and Emerging Adult Formation. Issue 1 (April 2020) - Setran, David
Looking at the challenges of emerging adult spiritual formation, it appears that faith is often disconnected from the process of identity formation taking place at this time of life. In order to foster spiritual formation, Christian educators can benefit from the insights of those writing about emerging adult "narrative identity, " the weaving together of past, present, and future experiences into a coherent life story. This article details some of the key insights of these theorists and articulates the need for emerging adults to form their own narrative identities with reference to the larger biblical story. It then offers a framework for how the biblical story can be "sown" in their lives through ritual, rhetoric, roles, and relationships.